2019
DOI: 10.1029/2019wr025316
|View full text |Cite
|
Sign up to set email alerts
|

Spatial‐Temporal Variation of Lake Surface Water Temperature and Its Driving Factors in Yunnan‐Guizhou Plateau

Abstract: Lake surface water temperature (LSWT) is an important factor of water ecological environment. In the context of global warming, the LSWT of global lakes generally reveals an upward trend. With a continuous intensification of human activities and a rapid expansion of the impervious surface, urbanization has exerted an increasing impact on the environment, so the impact of human activities on LSWT cannot be ignored. Because of the special geographical location, the change of LSWT in plateau lakes has important i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
64
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 130 publications
(66 citation statements)
references
References 50 publications
2
64
0
Order By: Relevance
“…The average altitude, average depth, and maximum depth of Dianchi Lake are 1885 m, 4.1 m, and 10.1 m, respectively. The average annual runoff of Dianchi Lake is 970 million m 3 , and the evaporation of lake surface is 430 million m 3 . The lake water supply is mainly based on land-to-lake volume, lake surface precipitation respectively, and three drinking water projects.…”
Section: Study Areamentioning
confidence: 99%
See 2 more Smart Citations
“…The average altitude, average depth, and maximum depth of Dianchi Lake are 1885 m, 4.1 m, and 10.1 m, respectively. The average annual runoff of Dianchi Lake is 970 million m 3 , and the evaporation of lake surface is 430 million m 3 . The lake water supply is mainly based on land-to-lake volume, lake surface precipitation respectively, and three drinking water projects.…”
Section: Study Areamentioning
confidence: 99%
“…The study area and the monitoring stations are shown in Figure 1. According to the published research results of the Dianchi Lake watershed [3], this paper mainly uses the improved normalized difference build-up index (INDBI) algorithm to extract the impervious surface. Civil vehicle ownership data, population data, and GDP data were mainly derived from the China statistical yearbook, Yunnan statistical yearbook [44], and the Kunming national economic and social development statistical bulletin [45].…”
Section: Historical Water Quality Data and Urbanization Datamentioning
confidence: 99%
See 1 more Smart Citation
“…In developing countries, investment in agricultural land has grown rapidly over the past two decades [31][32][33]. Myanmar, Congo and Colombia may be experiencing deforestation driven by rapid agricultural development [34].…”
Section: Introductionmentioning
confidence: 99%
“…Changes in land cover patterns have changed ecosystem functions and processes and have a significant impact on ES [4,5]. Although the provisioning services of ES have increased, the regulating services and biodiversity (BD) have degraded [6,7,8]. Countries or regions usually solve the problem of ecological damage by establishing nature reserves [9], and more than 12% of the earth’s land surface is designated as protected areas [10].…”
Section: Introductionmentioning
confidence: 99%